English learners’ attitudes towards developing reading strategies through scaffolding (Journal of Educational Sciences, 2023)
Reading skill is the ability of a person to read, understand and interpret the written words on a page of an article or other reading material. Many methods and techniques are used to develop reading strategies of English learners.Scaffolding is one of the most common methods in developing reading strategies of English learners. The current study examined the English learners’ attitudes towards developing their reading strategies with Scaffolding.The empirical study involved 47 students from Aisha Bibi High School (fall semester 2022-2023), 12 male and 35 female. The study was conducted to analyze students' attitudes towards developing reading strategies through scaffoldingg. The empirical study employs a quantitative research method.The results were obtained using The Statistical Package for the Social Sciences (SPSS) version 23.0. The Mann Whitney U-test was used to analyze descriptive results and to see differences between class and gender.The results of the analysis show that the attitude of learners of English was positive towards learning this subject. Statistically, there was no significant difference between the class and gender of participants in training.Keywords: Scaffolding, reading strategies, developing reading strategies, English learners’ attitudes.